Ceratozetes parvulus Sellnick 1922 - Behan-Pelletier, Valerie M.; Lindo, Zoë (Zenodo, 2019)
Ceratozetes parvulus Sellnick, 1922. Geographic Location : AK , Bushkana River (Behan-Pelletier 1985; Behan-Pelletier & Eamer 2004); Seward Peninsula, near to Cape Espenberg (66°28′22″N, 163°56′56″W) greyish tephra from Aniakchak eruption (Blackford et al. 2014); YT : Ivvavik NP, British Mtns, 69°17’N, 140°03’W (Behan-Pelletier & Bissett 1994); NT : peatlands (Behan-Pelletier & Bissett 1994); AB : peatlands (Behan-Pelletier & Bissett 1994); ABMI Site (Walter et al. 2014); MB : peatlands (Behan-Pelletier & Bissett 1994); ON : peatlands (Behan-Pelletier & Bissett 1994); Alfred bog (Behan-Pelletier & Eamer 2009). QC : Timmins 54°60’N, 67°00’W; northern region (Behan 1978a; as sp. nr.); peatlands (Behan-Pelletier & Bissett 1994); Poltimore bog; Parc national de la Gaspésie, Mont Albert; Lac Ford (Behan-Pelletier & Eamer 2009); NB : peatlands (Behan-Pelletier & Bissett 1994); Fundy NP (Behan-Pelletier & Eamer 2009); NS : Cape Breton Highlands NP (Behan-Pelletier 2010; Behan-Pelletier & Eamer 2009). NL : peatlands (Behan-Pelletier & Bissett 1994); Labrador, Forteau area (sp. nr.); Gros Morne NP, Yellow Marsh (Behan-Pelletier 1985; Behan- Pelletier & Eamer 2004). Habitats : peatlands; tundra with Sphagnum , lichen, Vaccinium sedge tussocks and moss at edge of stream; spruce, birch, and Shepherdia litter. Distribution : Holarctic. Published as part of Behan-Pelletier, Valerie M. & Lindo, Zoë, 2019, Checklist of oribatid mites (Acari: Oribatida) of Canada and Alaska, pp. 1-180 in Zootaxa 4666 (1) on page 133, DOI:10.11646/zootaxa.4666.1.1, http://zenodo.org/record/4000595